Water footprint in the construction process as an indicator of sustainability: a case study for Costa Rica - Mora-González, Alejandro (2024)
The main objective of the research was to determine the feasibility of using the Water Footprint (WF) as an environmental indicator in the construction sector, for which a field quantification of this indicator was carried out in four selected single-family housing residential projects in the Greater Area. Metropolitana de Costa Rica, seeing construction as a productive process, and analyzing the results by activity and globally. The direct blueprint in the construction process was calculated through field measurements, carrying out weekly inspections of each project, thus assigning a water consumption per activity according to the progress that was observed. The indirect water footprint (blue and green) for the materials was estimated, based on a series of data on the use of water in production, consulted from the available environmental declarations of each product. Due to the lack of data available in the national context, gray HH could not be estimated.  It is concluded that the results obtained could be considered as a first advance in the calculation of HH in the construction industry. To achieve a standard at the national level, it is necessary to encourage local producers or importers to develop environmental product declarations for construction materials and thus generate a robust database on water consumption in their production process. In addition, it is necessary to improve the practices of direct use of water in construction and the quantification of consumption as an indicator of efficiency in potential water savings.